2007
DOI: 10.1002/jcc.20813
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the reactions CF3CH2OCHF2 + OH/Cl and its product radicals and parent ether(CH3CH2OCH3) with OH

Abstract: A dual-level direct dynamic method is employed to study the reaction mechanisms of CF3CH2OCHF2 (HFE-245fa2; HFE-245mf) with the OH radicals and Cl atoms. Two hydrogen abstraction channels and two displacement processes are found for each reaction. For further study, the reaction mechanisms of its products (CF3CH2OCF2 and CF3CHOCHF2) and parent ether CH3CH2OCH3 with OH radical are investigated theoretically. The geometries and frequencies of all the stationary points and the minimum energy paths (MEPs) are calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
(69 reference statements)
2
8
0
1
Order By: Relevance
“…The electronic partition function is evaluated as where ϵ n is the electronic energy of the n th level and ω n is the correspondent degeneracy of that level. For the OH electronic partition function, we have included the two electronic states ( 2 Π 3/2 and 2 Π 1/2 ) resulting from the 139.7 cm –1 splitting of the 2 Π ground state. , Accordingly, the electronic partition function for the OH radical can be written − as , where c is the speed of light. For a single conformer structure, its overall rate constant (conformer-specific rate constant) can then be calculated as a sum over the n H individual reaction paths where σ i is the reaction path symmetry number and n H is the total number of hydrogen atoms in the molecule ranging from n H = 2 for R = CF 2 H to n H = 14 for R = CH 2 CH 2 CH 3 and CH­(CH 3 ) 2 .…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“…The electronic partition function is evaluated as where ϵ n is the electronic energy of the n th level and ω n is the correspondent degeneracy of that level. For the OH electronic partition function, we have included the two electronic states ( 2 Π 3/2 and 2 Π 1/2 ) resulting from the 139.7 cm –1 splitting of the 2 Π ground state. , Accordingly, the electronic partition function for the OH radical can be written − as , where c is the speed of light. For a single conformer structure, its overall rate constant (conformer-specific rate constant) can then be calculated as a sum over the n H individual reaction paths where σ i is the reaction path symmetry number and n H is the total number of hydrogen atoms in the molecule ranging from n H = 2 for R = CF 2 H to n H = 14 for R = CH 2 CH 2 CH 3 and CH­(CH 3 ) 2 .…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“… a The data are compiled from Luo, Zhou et al, Shang et al, Yang et al, Serinyel et al, Thion et al., and Cai et al …”
Section: Results and Discussionmentioning
confidence: 99%
“…The rate parameters were taken as analogous to the C−H primary sites of n-alkane + OH reactions as given by Sivaramakrishnan and Michael. The data are compiled from Luo, 40 Zhou et al, 29 Shang et al, 41 Yang et al, 42 Serinyel et al, 10 comparable branching ratios but with a slight T dependence. In line with Cai et al, 5 we observed that the contribution of the α(2°) channel decreases with increasing alkyl chain length in dialkyl ethers and thus an increase in the number of sites where hydrogen atoms can be abstracted.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the presence of an atom of Br, Cl, I etc. in an atmosphere is a chemical set back to ozone layer (Deka and Mishra, 2014;Laszlo et al, 1997;Wofsy et al, 1975;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%